Information Technology-Based Educational Video Model For Changes In Gingival Health Status In Adolescents - Ainul Auliyah A; Supriyana Supriyana; Bedjo Santoso; Endah Aryati Eko Ningtyas; Kusno Kusno (Syntax Corporation Indonesia, 2023)
The health problem that is often experienced by adolescents is dental and oral hygiene, RISKESDAS data for 2018, 57.6% of Indonesian people have dental and oral health problems. Gingival problems are common in adolescents. Lack of dental and oral hygiene causes gingival inflammation. Plaque, bacteria, and calculus that accumulate on the tooth surface are the main causes of periodontal disease. Early detection that is carried out independently as well as providing solutions for prevention and treatment to patients is very necessary. Media that is currently developing among adolescents is technology-based media which is increasingly creative and can be a solution for preventing dental disease. Proving appropriate information technology-based educational videos and their effective application to changes in gingival health status in adolescents. The research method used is Research and Development (RnD) with Quasy Experiment pre-test post-test control group design. Educational video based on information technology is appropriate for changes in gingival health status with the results of expert validation of 83% and p-value 0.044 and its application is effective in increasing knowledge (p=0.000), attitude (p=0.002), skills (p=0.000), GI (p = 0.001). As well as indicated by the delta value of knowledge (2.14), attitude (1.29), skills (2.14), decreased GI score (0.44) compared to the control group. Educational videos have proven to be appropriate and effective in their application to changes in gingival health status in adolescents marked by a decrease in the gingival index score.